Burkina Faso : Ex Post Assessment of Longer-Term Program Engagement-An Update. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Burkina Faso's ex-post assessment of longer-term program engagement. Economic growth has fluctuated above regional standards, averaging 5.3 percent between 2007 and 2012. The improvements in the agricultural sector, as a result of authorities' strong push for reforms, and investments in the sector, mitigated the impact of unfavorable weather conditions. Authorities responded to high commodity price pressure with temporary exemption from custom fees, value-added tax on basic products, sales of food at below market prices, and suspension of the automatic oil price mechanism. Inflation has remained generally low since 2010, despite food shortages caused by the drought in 2011.